2018
DOI: 10.3389/fpsyg.2018.01551
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of the Association Between Symbolic Approximate Arithmetic Performance and Basic Number Magnitude Processing Based on Task Difficulty

Abstract: Two types of number magnitude processing – semantic and spatial – are significantly correlated with children’s arithmetic performance. However, it remains unclear whether these abilities are independent predictors of symbolic approximate arithmetic performance. The current study addressed this question by assessing 86 kindergartners (mean age of 5 years and 7 months) on semantic number processing (number comparison task), spatial number processing (number line estimation task), and symbolic approximate arithme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Good symbolic number processing skills are characterized by fast and accurate responses. Symbolic number processing has been found to be a strong predictor of children's mathematics achievement across different grades in elementary school (Brankaer et al, 2017;Holloway & Ansari, 2009), and of approximate arithmetic performance (Wei et al, 2018), and arithmetic fluency (Banfi et al, 2024;Vanbinst et al, 2016, Träff, 2013. In their study, Banfi et al (2024) found number processing skills, assessed with dots and digits comparison tasks in grade 1, to predict arithmetic fluency in grades 2 and 3.…”
Section: The Role Of Domain-specific Skills In Arithmetic Fluency Dev...mentioning
confidence: 99%
“…Good symbolic number processing skills are characterized by fast and accurate responses. Symbolic number processing has been found to be a strong predictor of children's mathematics achievement across different grades in elementary school (Brankaer et al, 2017;Holloway & Ansari, 2009), and of approximate arithmetic performance (Wei et al, 2018), and arithmetic fluency (Banfi et al, 2024;Vanbinst et al, 2016, Träff, 2013. In their study, Banfi et al (2024) found number processing skills, assessed with dots and digits comparison tasks in grade 1, to predict arithmetic fluency in grades 2 and 3.…”
Section: The Role Of Domain-specific Skills In Arithmetic Fluency Dev...mentioning
confidence: 99%